STRATEGI PENGEMBANGAN HOME INDUSTRY DENGAN MENGGUNAKAN ANALISIS SWOT DAN METODE QSPM STUDI KASUS INDUSTRI SEPATU, SANDAL ETNIK DAN KULIT DI CV. DEALLOVA NUSANTARA HS - Muhamad Fajri; Ahmad Hipni; Metha Mutia (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
CV. Deallova Nusantara Hs is a home industry business engaged in the production of shoes, ethnic sandals and leather. The problem faced is the level of sales that is not stable until the level of sales decreases which is caused by internal and external factors in the company. The purpose of this study is to identify problems and analyze development strategies in CV. Deallova Nusantara Hs. Then provide a proposed development strategy with SWOT analysis and QSPM matrix. The research method used in this study is a qualitative approach by processing data starting from the input stage, data processing stage, and the decision-making stage to determine the strategy. The process of determining the strategy consists of processing IFE and EFE data, SWOT analysis, and the QSPM matrix for the formulation of strategies that will be used by CV. Deallova Nusantara Hs. Based on the results of the analysis carried out, it was obtained from the strength factor with the highest value of good service to consumers, the TAS score was 0.297, while the weakness factor with the lowest was the lack of advertisements for production publications, the TAS score was 0.1126, and the opportunity factor with the highest score was Collaborating with government agencies and companies. TAS is 0.4161, while the threat factor with the lowest score is the proliferation of innovative products from competitors with a TAS score of 0.2194